Effects of Floss Bands on Ankle Joint Range of Motion and Balance Ability - Byoung-Hyoun Moon; Ji-Won Kim (Korean Research Society of Physical Therapy, 2022)
Background: The range of motion (ROM) and balance ability of the ankle joint affect the stability of the ankle and prevent injuries or hurts from falling. In the clinical tests conducted recently, the floss band is widely used to enhance the range of joint motion and exercise performance, and there are many studies that have applied it to ankle joint increasing dorsi flexion (DF) angle.Objects: This study compared the effects on the range of ankle motion and static/dynamic balance ability of the ankle through three conditions (before floss band intervention, after floss band intervention, and after active exercise intervention) for adults.Methods: One intervention between floss band and active exercise was applied randomly and another intervention was applied the next day. After each intervention, the ROM of the ankle joints and the static balance was checked by measuring conducting one leg test. And the dynamic balance was checked by conducting a Y-balance test.Results: In the case of DF, the range of joint motion showed a significant increase after floss band intervention compared to before floss band intervention (p < 0.05). Static balance abil-ity showed a significant increase after the intervention of floss band and active exercise com-pared to before the intervention of floss band (p < 0.05). The dynamic balance ability showed a significant increase after the intervention of the floss band compared to before intervention of the floss band and after active exercise intervention (p < 0.05).Conclusion: Based on these results, it was confirmed that the application of floss band to the ankle joint increases DF and improves the static and dynamic balance ability. Based on this fact, we propose the application of a floss band as an intervention method to improve the ROM of the ankle joint and improve the stability of the ankle in clinical field.